2000
DOI: 10.1007/s100520000448
|View full text |Cite
|
Sign up to set email alerts
|

Unitarity and the QCD-improved dipole picture

Abstract: As a consequence of QCD factorization theorems, a wide variety of inclusive and exclusive cross sections may be formulated in terms of a universal colour dipole cross section at small $x$. It is well known that for small transverse size dipoles this cross section is related to the leading-log gluon density. Using the measured pion-proton cross section as a guide, we suggest a reasonable extrapolation of the dipole cross section to the large transverse size region. We point out that the observed magnitude and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
118
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(126 citation statements)
references
References 36 publications
8
118
0
Order By: Relevance
“…There is an extensive literature on the subject [39][40][41][42][43][44][45][46][47][48][49]. We will follow mostly Ref.…”
Section: Saturation Modelmentioning
confidence: 99%
“…There is an extensive literature on the subject [39][40][41][42][43][44][45][46][47][48][49]. We will follow mostly Ref.…”
Section: Saturation Modelmentioning
confidence: 99%
“…The main feature in a successful model is to be able to match the soft (low Q 2 ) and hard (large Q 2 ) regimes in a unified way. This has been achieved in models using Regge approach [4], QCD color transparency phenomena [5] and/or hybrid ones mixing nonperturbative functional approach and Regge phenomenology [6]. Phenomenological analysis including a parton saturation phenomenon at high energies has been considered, for instance in [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical studies performed using Eqs. (1) and (2) have demonstrated that interactions at the upper range of HERA energies in gluon-induced processes may be fairly close to the BBL in a wide range of impact parameters (see, e.g., [8,10]). This is consistent with an analysis [11] of current fits to HERA diffractive data, which leads to diffractive gluon densities which are significantly larger than the quark ones (see also [12]).…”
mentioning
confidence: 99%
“…It is essentially given by Eq. (10). Since the distributions in z (or equivalently u) do not depend on M, the jet distribution in z is given by…”
mentioning
confidence: 99%